Environmental noise and management : overview from past to present - Kurra, Selma (Wiley series in acoustics noise and vibration, 2021)
"Environmental Noise and Management provides a comprehensive overview of environmental noise pollution, and begins by covering the fundamentals of noise and acoustics, major noise sources and prediction and evaluation techniques. Developments in noise measuring techniques, and mapping and improvement of legislation to control noise pollution are then discussed, and international regulations are presented. Technological advances and recent developments regarding strategy and action plans are also covered in depth, Environmental Noise and Management is a comprehensive resource for researchers and graduate students who are involved in noise pollution from the standpoint of environmental impact and control. Noise is frequently described as 'unwanted sound', and, within this context, environmental noise is generally present in some form in all areas of human activity. The adverse effects of noise exposure (i.e. noise pollution) could include: interference with speech or other 'desired' sounds, annoyance, sleep disturbance, anxiety, hearing damage and stress-related cardiovascular health problems. As a result, environmental noise is studied, regulated and monitored by many governments and institutions, as well as forming the basis or branch for a number of different occupations"--